Risk Factors in Intraepithelial Lesions of the Cervix - Martha Palma Osorio; Alejandro David Romero Flores; Ana Isabel Torres Mesa (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Foundation: the risk factors of intraepithelial lesions behave similar to those of cervical cancer. Objective: to identify the influence of different risk factors related to the appearance of intraepithelial lesions of the cervix. Method: an observational case-control study was carried out in the Gustavo Aldereguía Teaching Polyclinic of the Granma province in the period from January 1, 2016 to June 30, 2017. The 105 patients with cervical intraepithelial neoplasia were defined as cases histopathologically confirmed and as controls to women who underwent the cytological test, selected by simple random sampling. Each patient was performed: interview, physical examination and diagnostic means. For the analysis of risk factors, a univariate and multivariate strategy was used. Explanatory variables were defined as factors considered as hypothetically risky which would be subject to evaluation. The appearance of intraepithelial neoplasia was considered as a response variable. Punctual and 95 % confidence interval estimates were obtained. Results: vaginal sepsis and early menarche were noticeable, however not the use of condoms, human papillomavirus infection, oral contraception, age, intrauterine device and smoking as indifferent factors. Erosion and vaginal sepsis were the most significant due to the logistic regression model. There were interactions between cervicitis, multiple sexual partners and smoking; moderately significant were age and early menarche; cervicitis and erosion, human papillomavirus infection and multiple sexual partners. Conclusions: it was determined that vaginal sepsis and cervical erosion presented a statistically significant and important association with the probability of the appearance of intraepithelial lesions of the cervix.